Tingkat Kesadaran Generasi Muda Terhadap SDGs - Muhammad Satria Aji Pamungkas (Casuarina: Jurnal Teknik Lingkungan, 2024)
Sustainable development is a principle that prioritizes achieving human development while maintaining natural systems to ensure that society remains dependent on nature and the resources it contains. This research aims to obtain conclusions regarding the extent to which the younger generation is aware of the SDGs with 17 indicators in the tertiary sector. The research method used in this research is a quantitative method using research instruments in the form of questionnaires. This research was conducted using a questionnaire to collect data, and covers all 17 SDGs. Consists of 51 closed-ended questions covering a variety of current social, economic and environmental topics. Determining the population sample size was calculated using the Slovin formula, so that 67 active students of the biology study program were obtained as respondents in this research. The overall level of awareness of students in the biology study program at UIN Sunan Ampel Surabaya is relatively high, this is shown by students who have high knowledge and a positive attitude. It is recommended that the introduction of SDGs to students needs to be deepened, this can be done by adding new courses related to global goals and sustainable development.